The Influence of International or Local Student Status on Generation Z's Decision to Move Abroad (International Forum of Researchers and Lecturers, 2025)
Globalization and the internationalization of higher education have significantly increased student mobility. Generation Z, growing up in the digital era, exhibits unique characteristics and career aspirations. This study aims to analyze how the status as an international student compared to a local student influences the intention of Generation Z students to move abroad after graduation. Using a qualitative case study approach, this research collected data through a questionnaire distributed at two universities, focusing on two representative respondents: one international student and one local student. Thematic analysis was used to explore the motivations, barriers, and career aspirations shaping their mobility decisions. Preliminary results indicate that international students tend to have higher transnational capital and stronger global career aspirations, while local students give more consideration to family ties and stability, although they remain open to international opportunities if the incentives are strong. These findings provide insights for educational institutions and policymakers in designing strategies to support and manage the mobility of young talent in the future.